A random walk down Maple Lane? A critique of neoclassical consumption theory with reference to housing wealth - Greg Hanssgen (Levy Economics Institute of Bard College, 2006)
The development of the permanent income/life cycle consumption hypothesis was a key blow to Keynesian and Kaleckian economics, and, according to George Akerlof, it set the agenda for modern neoclassical macroeconomics. This paper focuses on the relationship of housing wealth to neoclassical consumption theory, and in particular, the degree to which homes can be treated collectively with other forms of permanent income. The neoclassical analysis is evaluated as a partly normative and partly positive one, in recognition of the dual function of the neoclassical theory of rationality. The paper rests its critique primarily on the distinctive role of homes in social life; theories that fail to recognize this role jeopardize the social and economic goods at stake. Since many families do not own large amounts of assets other than their places of residence, these issues have important ramifications for the relevance of consumption theory as a whole.
Keywords: A13; B40; B50; E21; 330; Consumption theory; theories of rationality; positive/normative distinction; liquidity constraints